Image and power in Tudela during the Renaissance - Soria Magaña, Jesús (Huarte de San Juan. Geografía e Historia, 2011)
Along the 16th century Tudela was a witness of a series of events that placed between the biggest cities in northern Spain, both in artistic context, politician and socioeconomic. The city council wanted to place the city in a favorable situation during this century, so do not hesitate to sponsor works or celebrations that helped to be between the most important populations in northern Spain.